2020
DOI: 10.1186/s12939-020-01268-3
|View full text |Cite
|
Sign up to set email alerts
|

Tenofovir for prevention of mother to child transmission of hepatitis B in migrant women in a resource-limited setting on the Thailand-Myanmar border: a commentary on challenges of implementation

Abstract: Background The aim of this manuscript is to highlight challenges in the implementation of maternal tenofovir disoproxil fumarate (tenofovir) for prevention of mother to child transmission (PMTCT) of hepatitis B virus (HBV) in resource limited setting. Current preventive strategies in resource-limited settings fail mainly due to prohibitive costs of hepatitis B immunoglobulin (HBIG) and a high proportion of homebirths, meaning both HBIG and hepatitis B birth dose vaccine are not given. A new strategy for PMTCT … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…Delivering hepatitis care is challenging in resource‐limited settings, particularly in conflict zones and humanitarian crises where health systems are fragile. However, it is feasible to provide treatment for HIV in conflict‐affected regions 59 and prevent mother‐to‐child transmission of HBV with tenofovir in resource‐limited settings 60 …”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Delivering hepatitis care is challenging in resource‐limited settings, particularly in conflict zones and humanitarian crises where health systems are fragile. However, it is feasible to provide treatment for HIV in conflict‐affected regions 59 and prevent mother‐to‐child transmission of HBV with tenofovir in resource‐limited settings 60 …”
Section: Discussionmentioning
confidence: 99%
“…However, it is feasible to provide treatment for HIV in conflict-affected regions 59 and prevent mother-to-child transmission of HBV with tenofovir in resource-limited settings. 60 In conclusion, hepatitis B is a significant public health issue with a high burden in LMIC, where service delivery is challenging in the…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Prophylactic treatment of pregnant mothers with antiviral treatment during gestation has previously been proposed as an alternative solution in eliminating mother-to-child-transmission in underserved populations [74]. In remote regions along the border of Thailand and Myanmar, Bierhoff et al demonstrated promise in prophylactic daily antiviral therapy started early in gestation as a substitute for mothers who are unable to access immunoglobulin or vaccines with a facility birth [75]. This indication for prophylactic tenofovir use was also used in Thompson et al [76].…”
Section: Th Pillar: Reducing Infectivity With Enhanced Treatment Reco...mentioning
confidence: 99%
“…Forty percent of the existing studies (n = 10) were made in the Shoklo Malaria Research Unit (SMRU) on the Thai-Myanmar border that has a long and complicated history of conflict and human displacement. Shoklo Malaria Research Unit has provided humanitarian health care for refugees since 1986 and for migrants since 1997 [8,10,[21][22][23][24][25][26][27][28].…”
Section: Health and Well-beingmentioning
confidence: 99%